Cerebrospinal Fluid Biomarker Candidates for Parkinsonian Disorders - Constantinescu, Radu; Mondello, Stefania (Frontiers in Neurology, 2013)
The parkinsonian disorders are a large group of neurodegenerative diseases including idiopathic Parkinson's disease (PD) and atypical parkinsonian disorders, such as multiple system atrophy, progressive supranuclear palsy, corticobasal degeneration, and dementia with Lewy bodies. The etiology of these disorders is not known although it is considered to be a combination of genetic and environmental factors. One of the greatest obstacles for developing efficacious disease-modifying treatment strategies is the lack of biomarkers. Reliable biomarkers are needed for early and accurate diagnosis, to measure disease progression and response to therapy. In this review several of the most promising cerebrospinal biomarker candidates are discussed. Alpha synuclein seems to be intimately involved in the pathogenesis of synucleinopathies and its levels can be measured in the cerebrospinal fluid and in plasma. In a similar way, tau protein accumulation seems to be involved in the pathogenesis of tauopathies. Urate, a potent antioxidant, seems to be associated to the risk of developing PD and with its progression. Neurofilament light chain levels are increased in atypical parkinsonian disorders compared with PD and healthy controls. The new "omics" techniques are potent tools offering new insights in the patho-etiology of these disorders. Some of the difficulties encountered in developing biomarkers are discussed together with future perspectives.